Proportion of chronic kidney disease in rheumatoid arthritis patients, in a tertiary level hospital - Morshed, Mamun; Shahidullah, Muhammad; Shahinuzzaman, Mridha Mohammad; Masud, Mahadi (International Journal of Research in Medical Sciences, 2025)
Background: Chronic kidney disease (CKD) is a significant but often overlooked complication in rheumatoid arthritis (RA) patients, influenced by systemic inflammation, medication-induced nephrotoxicity, and comorbidities such as hypertension and anemia. The purpose of this study was to determine the proportion of chronic kidney disease among rheumatoid arthritis patients in a tertiary-level hospital. The aim of the study was to determine the proportion of chronic kidney disease among rheumatoid arthritis patients in a tertiary level hospital. Methods: This cross-sectional study at the Department of Medicine, Sir Salimullah Medical College and Mitford Hospital, Dhaka (January to December 2015), included 50 RA patients (2010 ACR/EULAR criteria). Data analyzed using SPSS (t-tests, chi-square, logistic regression; p<0.05). Ethical approval obtained. Primary outcomes: CKD proportion in RA and its associations. Results: In this study of 50 rheumatoid arthritis (RA) patients, the mean age was 47.4±14.7 years, with a female predominance (60.0%). Chronic kidney disease (CKD) was present in 22.0% of patients. Most CKD cases were in stages 3a (36.4%) and 3b (45.5%). CKD patients had a significantly longer RA duration (5.35±3.24 years vs. 2.60±1.67 years, p=0.044) and higher prevalence of hypertension (45.0% vs. 12.8%, p=0.017) and anaemia (100% vs. 61.5%, p=0.014). The majority (90.9%) of CKD patients used a combination of NSAIDs and DMARDs. Conclusions: CKD was proportioned in 22% of RA patients, primarily in stages 3A and 3B, with longer RA duration as a key risk factor.